Peran Kepuasan Kerja dalam Memediasi Dampak Reward dan Punishment Terhadap Kinerja Mitra Driver Gojek di Jabodetabek - Faif Yusuf; Nurzalinar Joesah; Jeffry Latumahina (CV. ULIL ALBAB CORP, 2024)
This study aims to examine the role of job satisfaction in mediating the impact of Rewards and punishments on the performance of Gojek partner drivers. Rewards and punishments are two important aspects of human resource management that can influence employee performance. However, the relationship between Rewards, punishments, and performance is not always direct, and job satisfaction often plays a significant mediating role. The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to 97 Gojek partner drivers in the Jabodetabek area. The data analysis technique used is path analysis to test the direct and indirect relationships between Rewards, punishments, job satisfaction, and performance. The results show that Rewards have a positive and significant impact on driver partner performance. Conversely, punishments have a negative and significant impact on their performance. In addition, Rewards also have a positive and significant effect on job satisfaction, while punishments have a negative and significant effect on job satisfaction. Job satisfaction was found to have a positive and significant influence on the performance of partner drivers. The study also found that job satisfaction mediates the influence of Rewards and punishments on the performance of partner drivers. Good Rewards increase job satisfaction, which in turn improves performance. Conversely, excessive punishments reduce job satisfaction, which ultimately decreases performance.